(untitled) (Texas Journal of Medical Science, 2022)
The tourism industry is one of the sectors that is greatly affected by COVID-19 pandemic. Data for the review was generated from desk review of secondary materials such as online blogs, and primary data such as observation and interview through social media chat. The study adopted a descriptive – survey design with simple tabulation and t-test analysis for testing of stated hypothesis. Findings of the study revealed that the outbreak of pandemic disease led to rapid shutdowns in cities and states across Nigeria, which greatly affected the tourism and hospitality industry in particular. This pandemic showed the rapid negative impact on the tourism and hospitality marketing in particular and the industry at large. The findings revealed that COVID-19 has increased cancellations of reservations of various kinds, hotels and travel bookings resulted in revenue loss and unemployment situations, as well as loss of substantial revenue to the government and increasing incidence of poverty among others. The paper recommends that provision of alternative service and diversification of services, as well as product consumption and compensation to business operators in the hospitality and tourism sector to return back to normal operations is a key factor in salvaging the situation in Nigeria.